2015
DOI: 10.1094/pdis-04-14-0391-re
|View full text |Cite
|
Sign up to set email alerts
|

Expanded Host Range Testing forVerticillium nonalfalfae: Potential Biocontrol Agent Against the InvasiveAilanthus altissima

Abstract: The naturally occurring Verticillium nonalfalfae has been proposed as a biocontrol agent against the highly invasive Ailanthus altissima in the eastern United States. We tested 71 nontarget woody species for susceptibility to the potential biocontrol agent. In the field, only devil’s walkingstick (17% incidence) and striped maple (3%) acquired infections through natural spread from infected A. altissima (100%). Staghorn sumac (16% incidence) also exhibited wilt in close proximity to diseased Ailanthus, althoug… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
63
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 35 publications
(79 citation statements)
references
References 34 publications
14
63
2
Order By: Relevance
“…This phenomenon has been reported in olive as re-growth from existing crowns that suffer from limited dieback, or from the stem base after complete dieback (López-Escudero Recovery has similarly been reported in Catalpa bignonioides and Sassafras albidum (Kasson et al 2015) as re-growth from the crown, in Acer platanoides with re-growth from stem base after extensive dieback (Goud et al 2011), and in Fraxinus excelsior as regrowth without dieback of twigs (Hiemstra 1998b). The inherent structure of the xylem and the ability of trees to produce new layers of xylem has a significant impact on the potential of recovery (Banfield 1968;Emechebe et al 1974;Sinclair et al 1981;Tippett and Shigo 1981).…”
Section: Reactions Of Infected Trees and Recoverymentioning
confidence: 61%
“…This phenomenon has been reported in olive as re-growth from existing crowns that suffer from limited dieback, or from the stem base after complete dieback (López-Escudero Recovery has similarly been reported in Catalpa bignonioides and Sassafras albidum (Kasson et al 2015) as re-growth from the crown, in Acer platanoides with re-growth from stem base after extensive dieback (Goud et al 2011), and in Fraxinus excelsior as regrowth without dieback of twigs (Hiemstra 1998b). The inherent structure of the xylem and the ability of trees to produce new layers of xylem has a significant impact on the potential of recovery (Banfield 1968;Emechebe et al 1974;Sinclair et al 1981;Tippett and Shigo 1981).…”
Section: Reactions Of Infected Trees and Recoverymentioning
confidence: 61%
“…Also, some tree species such as olive, cherry, apricot, peach, cacao, catalpa, sassafras, and ash are able to recover from Verticillium wilt; a capability in which the anatomy of the xylem is reported to play an important role (Banfield 1968;Emechebe et al 1974;Hiemstra and Harris 1998;Sinclair et al 1987;Tippett and Shigo 1981;Kasson et al 2015). However, although Kasson et al (2015) recently reported reisolation of V. nonalfalfae from the stem of red and sugar maple up to 4 years after inoculation, the fate of V. dahliae in recovered trees in the years following the initial infection is unknown. Notably, in naturally infected trees this aspect is difficult to investigate because every year new upward surges of the pathogen from infected roots are possible, as well as new infections from the soil.…”
Section: Discussionmentioning
confidence: 99%
“…Compartmentalization resulting from the inherent structure of the wood, in combination with changes in anatomy and chemistry of xylem after infection, was suggested to play important roles in protecting trees against colonization by vascular pathogens (Bonsen et al 1985;Manion 2003;Shigo 1984;Tippett and Shigo 1981;Smith 2006). However, although recovery from Verticillium wilt has been described not only for ash, but also for other tree species including almond and peach (Ciccarese et al 1990), apricot (Taylor and Flentje 1968;Vigouroux and Castelain 1969), pistachio (Paplomatas and Elena 1998), cocoa (Emechebe et al 1974), avocado (Latorre and Allende 1983), olive (López-Escudero and Blanco-López 2005), catalpa and sassafras (Kasson et al 2015), there is little information about the fate of the fungus in infected trees in the years following the initial infection. Recently, Kasson et al (2015) reported that V. nonalfalfae could be isolated from asymptomatic red and sugar maple several years after inoculation.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Concurrently, 64 seeds with samaras per seed source for each of two seed-producing trees and 43 and 40 seeds per seed source for two additional seed-producing trees previously collected in Pennsylvania from 2008-2010 from female Ailanthus trees [1,24] were treated similarly (Table 1). For both germination studies, the seed/soil mix was maintained at 1.7 • C for 28 days, as previously reported [24], after which seeds were placed into seed flats containing additional potting mix, transferred to a greenhouse, and misted daily until initial germination was observed. Upon germination, individual seedling wells were labeled with date of germination.…”
Section: Germination Studies To Assess Seed Viability Based On Tree Amentioning
confidence: 99%